RESULTS OF SURGICAL CORRECTION OF POSTOPERATIVE COMPLICATIONS IN ANORECTAL MALFORMATION IN CHILDREN - А. Хамраєв; Д. Рахманов; У. Хамроєв (Bukovynian State Medical University, 2023)
The high frequency of postoperative complications (POС) in the anorectal zone remains an urgent problem of pediatric surgery. Satisfactory results after a single intervention are 50-80%. After the correction of anorectal postoperative malformation (APM), functional disorders of the sphincter apparatus of the rectum are observed in 30-60% of patients, which further leads to fecal incontinence (FI) and chronic constipation (CC). We retrospectively analyzed the causes of the most common recurrent pathological conditions in the anorectal zone in children as well as tactical approaches, methods of software correction, and considered ways to prevent them. The aim. The goal is to improve the results of surgical correction of postoperative complications (POC) in the anorectal zone in children. Material and methods. 78 patients with POC in the anorectal zone after primary and repeated correction of anorectal malformations (ARM) were examined. 197 reconstructive operations were performed. The diagnostic algorithm consisted of clinical, X-ray, laboratory examination, MRI and endoscopic examination methods. The study has been carried out in accordance with the principles of the Helsinki Declaration. The research protocol was approved by the Local Ethics Committee (LEK) of all participating institutions. The informed consent of the children's parents was obtained for the research. The authors declare that there is no confl ict of interest. Statistical processing of the study results was carried out using standard methods with the calculation of the absolute number of observations (n) and the percentage ratio (%). Results and discussion. The analysis of long-term results after the primary and repeated correction of the ARM showed that unreliable primary diagnosis, inadequate preoperative preparation, and the choice of the operation method led to the development of postoperative anal sphincter insuffi ciency (PASI), which required a large number of repeated operations. The causes of complications were studied, errors were analyzed, indications, timing, accesses, volume and methods of repeated surgery were optimized. The optimization of tactical approaches, methods of surgical and rehabilitation treatment led to the improvement in the results of treatment of PASI up to 85.3%. Conclusions: 1. Indications and the choice of method for repeated correction of pathological conditions in the anorectal zone in children are determined taking into account the degree of PNAS. 2. Analysis of the causes of errors, optimization of diagnostics, tactics of intraoperative surgical correction and postoperative preventive measures contribute to improving the results of treatment of children. 3. Optimization of tactical approaches, methods of surgical and rehabilitation treatment led to an improvement in the results of treatment of PNAS up to 85.4%.